(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate the thiol-disulfide balance, role of oxidative stress in pneumonia and role of measurement of thiol as a new biological marker for the diagnosis of pneumonia in children with pneumonia who admitted to pediatric emergency service and general pediatric polyclinic.Material and Methods: In our study, patients between 6 months and 4 years of age, who admitted to the Pediatric Emergency Department and Pediatric Policlinic of between January 2017 and February 2018 with a diagnosis of community-acquired pneumonia, were evaluated prospectively. A total of 90 patients were included in the study, including 45 patients and 45 healthy children in the same age group. These patients were examined for age, gender, symptoms and physical examination findings, native thiol, total thiol and disulfide values. Results: There was no significant difference between the patient and control groups in terms of gender. Statistically significant difference was observed between native thiol, total thiol and disulfide values between patient and control group (p0.05). In the patient group, the levels of native thiol and total thiol were low and disulfide levels were found to be high. There was a significant difference between patient and control group in terms of disulfide / total thiol, disulfide / native thiol and native thiol / total thiol parameters (p0.05). Disulfide / total thiol and disulfide / native thiol parameters were high in the patient group. Nativethiol / total thiol ratio was found to be high in the control group. Conclusion: In children with pneumonia; native thiol, total thiol, disulfide and their ratios were found to be significantly correlated. It was found that oxidative stress has an important role in the pathogenesis of pneumonia. The use of thiols in the diagnosis of pneumonia may guide clinicians.